Empowerment of married women for social changes in a selected community of Kathmandu valley (Journal of Patan Academy of Health Sciences, 2018)
Introductions: Empowerment of women is the process by which women gain power and control over their own lives and acquire the ability to make  choices and decisions. It influences the direction of social change and create a healthy life of self as well as for family. This study aimed to assess the level of empowerment of married women and association with demographic variables.Methods: A cross-sectional study was carried out among married women with children and living with husband, at Kumbhesor ‘tole’ (community) in ward number 11 of Lalitpur Metropolitan City in Kathmandu valley, Nepal, during Jul-Aug 2017. Purposive sampling technique was used. Data were collected through interview using structured questionnaire by door to door visit in community.Results: Total 170 women were interviewed. High level empowerment (score >70%) was seen in 111 (64.5%) and low level empowerment (score ≤50%) in 9 (5.5%) women. Overall empowerment was 75.7±12.3, highest in the dimension of ‘health care decision making’ (82.3±10.5), lowest in ‘educational decision making’ 59.8±21.6. Family type, respondents’ and husband’s educational status had significant association with empowerment.Conclusions: The finding showed that most of the married women in urban community had high empowerment with highest decision making power on health care dimension. Family type and educational status of women and husband were associated factors.